Respostas
respondido por:
1
Vamos la´:
p² - 6p + 9 = 16
Fatorando :
(p - 3)² = 16
Resolvendo :
p - 3 = ± √16
p - 3 = ± 4
p = 3 ± 4
Raízes :
p' = 3 + 4 = 7
p'' = 3 - 4 = - 1
Solução :
S = {-1,7}
Espero ter ajudado !!
p² - 6p + 9 = 16
Fatorando :
(p - 3)² = 16
Resolvendo :
p - 3 = ± √16
p - 3 = ± 4
p = 3 ± 4
Raízes :
p' = 3 + 4 = 7
p'' = 3 - 4 = - 1
Solução :
S = {-1,7}
Espero ter ajudado !!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás